Implementing collaborative learning platforms for healthcare quality improvement in Lao PDR: a case study of national forums - Shinsuke Murai; Bounnack Saysanasongkham; Goro Nishimoto; Somchanh Thounsavath; Satoko Jimbo; Shiho Hansen; Miwa Kanda; Aki Hashizume; Sommana Rattana; Somyoth Duangphachanh; Vanpheng Phanthanalay; Anousone Sisoulath; et al. (BMC Health Services Research, 2026)
Abstract Background Healthcare quality and safety initiatives in low- and middle-income countries often face fragmentation due to varying stakeholders’ readiness levels. Collective learning facilitates knowledge exchange and institutional capacity building, which are crucial for overcoming organizational constraints in quality improvement (QI) implementation. However, its feasibility and effectiveness in resource-limited settings remain to be studied. This study examined the feasibility and effectiveness of collaborative learning forums for healthcare QI in Lao PDR implemented through the Japan International Cooperation Agency project. Methods This descriptive case study analyzed four dimensions of collaborative learning forums using existing documentation: participant engagement (overall and self-funded participation), learning environment (topic evolution, QI activity distribution, and participant feedback), QI readiness, and the role of international cooperation. Inductive qualitative analysis was conducted to extract key lessons, and deductive analysis applied a framework for knowledge transfer readiness to assess QI readiness. QI activities were classified using a Japanese QI typology: problem solving, task achievement, countermeasure implementation, and prevention. Results Over four years, participation increased from 65 to 234 attendees and from 14 to 97 institutions, with self-funded participation rising from 7.7% to 52.1%. Survey responses indicated that 89.0% were willing to recommend a forum to their colleagues. Discussion topics evolved from policy implementation and QI methods to broader issues such as hospital governance, patient safety, and crisis response. Problem solving was the dominant QI approach, followed by task achievement, countermeasure implementation, and prevention. However, 19.5% of efforts remained in the situational assessment stage, especially on patient and staff satisfaction. Conclusions A structured collective learning platform can enhance QI readiness in low-resource settings by fostering shared understanding and promoting iterative learning. To maximize its potential, it is essential to cultivate local ownership, engage multilevel leadership, and create culturally aligned learning environments that empower local actors. Such environments should not rely on rigid tools or externally led solutions but enable teams to explore and adapt approaches to their context. International cooperation may need to initially provide support but gradually shift towards facilitation, especially in centralized governance systems, helping to sustain QI efforts through local adaptation and long-term integration into health systems.